THE USE OF INTERNET TECHNOLOGIES IN MEDICAL EDUCATIONAL SCHOOLS - Iliasova, Yuliia; Shevchenko, Ludmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article emphasizes the need for the application of innovative Internet technologies in medical schools. The authors submit some practical aspects of using educational blog Blogger, mental maps Mindomo and application Learning Apps in training of medical students when they study the professional disciplines. The results of a survey of would-be doctors and junior medical staff are described. They prove the effectiveness of the use of blogs, mental maps and online exercises by means of Learning Apps in studying of professional disciplines. The purpose of the article is to highlight the methodology and results of experimental work aimed at the verification of the effectiveness of using of innovative Internet technologies in medical schools. The experimental verification of the effectiveness of the introduction innovative Internet technologies on the training of future junior medical staff in study of special disciplines is presented. It was specified that future doctors and junior medical staff of the experimental groups at the formative stage of the experiment received better results, than the students of the control groups and they have a higher level of readiness for professional activity. The statistical verification also confirmed the effectiveness of the implementation of Internet technologies.